SETTING AND CHARACTERIZATION OF GEOLOGICAL UNITS FROM LAND NUMERICAL MODEL IN THE DISTRICT OF JUAN VIÑAS, CARTAGO - Zúñiga-Mora, Héctor (2016)
Geological units of the district of Juan Viñas were established based on the use of a land numerical modeling as a form of zoning the studying area. Such modeling involved the use of vector contour lines to create the MED which served as the basis for the shaded relief map where the geological units were delimited. Additionally, some tests and sample collection for the basic macroscopic description and thin sections were performed in order to establish the petrographic nature of the lithological materials that were found. Ten geological units mainly related to lava flows, thus identifying flows generated from a single point of emission, lineal emissions through cracks or subconical domes were suggested. These units were covered with surface deposits that may correspond to wheathered ash deposits. Valley units and alluvial terraces, possible tectonic scarps and massive flow deposits have been also identified.